The design of a refrigerated semi-trailer using advanced composites - Strydom, Ockert Jacobus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.